2012
DOI: 10.3109/08923973.2011.648270
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Jun N-terminal kinase and nuclear factor κ B pathways mediates fisetin-exerted anti-inflammatory activity in lipopolysccharide-treated RAW264.7 cells

Abstract: Although fisetin, a natural flavonoid, was known to inhibit proliferation, carcinogenesis and inflammation, the underlying anti-inflammatory mechanism of fistein still remains unclear. Thus, in the present study, the anti-inflammatory mechanism of fisetin was investigated in association with mitogen-activated protein kinase (MAPK) and nuclear factor κ B (NF-κB) pathways in lipopolysaccharide (LPS)-stimulated RAW264.7 mouse macrophages. We found that fisetin significantly reduced the nitrate oxide (NO) producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 47 publications
(53 reference statements)
4
28
1
Order By: Relevance
“…Previous research indicated that fisetin may protect against the progression of inflammatory diseases by limiting interactions between mast cells and activated T cells [14]. Recently, it has been reported that fisetin exerts anti-inflammatory effect by inhibiting c-Jun N-terminal kinase (JNK) and NF-κB pathways in LPSstimulated RAW264.7 macrophage cells [12]. Furthermore, it has been shown that fisetin can inhibit lipopolysaccharide-induced macrophage activation and dendritic cell maturation [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research indicated that fisetin may protect against the progression of inflammatory diseases by limiting interactions between mast cells and activated T cells [14]. Recently, it has been reported that fisetin exerts anti-inflammatory effect by inhibiting c-Jun N-terminal kinase (JNK) and NF-κB pathways in LPSstimulated RAW264.7 macrophage cells [12]. Furthermore, it has been shown that fisetin can inhibit lipopolysaccharide-induced macrophage activation and dendritic cell maturation [15].…”
Section: Introductionmentioning
confidence: 98%
“…1) is a member of flavonoids, and it is commonly found in plants such as smoke trees and various types of fruits and vegetables such as strawberries, grapes, apples, persimmons, onions, and cucumbers. Various in vitro and in vivo studies have shown that fisetin exerts wide pharmacological properties such as anticancer [9], antioxidant [10], and antiinflammation [11][12][13]. Previous research indicated that fisetin may protect against the progression of inflammatory diseases by limiting interactions between mast cells and activated T cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…At present, fisetin has shown multiple biological activities including anti-proliferative (7,8), pro-apoptotic (9-13), neuroprotective (14) and anti-oxidative activities (15). Moreover, fisetin has been shown to suppress the proliferation of a wide variety of tumor cell, including prostate cancer (16), liver cancer (17), colon cancer (18) and leukemia (19) cells, and inhibit the mitogen-activated protein kinase (MAPK) and nuclear factor (NF)-κB signaling pathways in various type of cancer cell, such as colon and pancreatic cancer (14,(20)(21)(22)(23)(24). Fisetin was also reported to reduce the invasive and migratory capacity of the A549 human lung cancer cell line via the extracellular signal-regulated kinase (ERK) signaling pathway (25).…”
Section: Introductionmentioning
confidence: 99%
“…However, signaling pathways other than Erk MAPK have also been implicated in fisetin-induced cellular activation. For example, in LPS-stimulated RAW264.7 macrophages, decreased phosphorylation of JNK and IκBα, but not Erk and p38 MAPK was found (13,30). Interestingly, fisetin also attenuates IκBα and p38 MAPK phosphorylation in LPS-stimulated microglia (31).…”
Section: Discussionmentioning
confidence: 98%